MAKNA BUBUR SURA DALAM TRADISI BUKA LUWUR MAKAM SUNAN KUDUS PRESPEKTIF BUDAYA - Moh Rosyid (Lembaga penelitian dan pengabdian kepada Masyarakat, 2020)
This article describes the tradition of buka luwur which is a cloth that protects the tomb of Sunan Kudus which is commemorated by replacing the new flexural tradition in the Buka Luwur tradition every year. The tradition is carried out by the Foundation Board of the Mosque, the Tomb, and Menara Sunan Kudus in Central Java with the people of Kauman Village, Kota District, Kudus every month Muharam/Sura. The purpose of writing this article is to explore the symbolic meaning of Bubur Sura, which is located in the complex of the Tomb of Sunan Kudus, behind the Masjid al-Aqsa Menara Kudus. This research data were obtained by interview, participatory observation, and literature review. Data collection was analyzed using a qualitative descriptive approach. The tradition of open flexible has a characteristic that is the distribution of Asura porridge, nasi jangkrik, Islamic art attractions that are displayed to the public, and the replacement of old luwur with the new one. The meaning Bubur Sura to reference UU Nomor 5 Tahun 2017 tentang cultural progresiive, bubur sura tradition have mean tolerance, diversity, locality, between regions, partisipative, the benefits, sustainability, expretion freedom, coherent, equality, and mutual cooperation. Preserved tradition expressed to pray and care for ancestors, Sunan Kudus.